Continuous high-repetition-rate operation of collisional soft-x-ray lasers with solid targets - Rocca, Jorge J., author; Marconi, M. C., author; Alessi, D., author; Luther, B. M., author; Wang, Y., author; Larotonda, M. A., author; Weith, A., author; Optical Society of America, publisher (Colorado State University. Libraries, 2006)
We have generated a laser average output power of 2 μW at a wavelength of 13.9 nm by operating a tabletop laser-pumped Ni-like Ag laser at a 5 Hz repetition rate, using a solid helicoidal target that is continuously rotated and advanced to renew the target surface between shots. More than 2×104 soft-x-ray laser shots were obtained by using a single target. Similar results were obtained at 13.2 nm in Ni-like Cd with a Cd-coated target. This scheme will allow uninterrupted operation of laser-pumped tabletop collisional soft-x-ray lasers at a repetition rate of 10 Hz for a period of hours, enabling the generation of continuous high average soft-x-ray powers for applications.